PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA MELALUI PEMBELAJARAN KOOPERATIF TIPE STAD SISWA KELAS VII-I SMP NEGERI 3 KERTOSONO - Sholihah, Aimmatus (Al Tadib : Jurnal Ilmu Pendidikan, 2016)
Action Research this class as one of the efforts in the process of learning mathematics through the implementation of cooperative learning model type STAD, this type has a system of grouping small ie 4 students are heterogeneous, according to the problems faced by students, among others: The low activity of students in activities learning, poor learning outcomes of students in learning mathematics. This class action research, aims to increase the activity and results of learning mathematics. VII-I grade students of SMP Negeri 3 Kertosono. With the implementation procedure of Class Action Research consists of three cycles, each cycle consists of four stages, namely Planning, Implementation, Observation and Reflection. Based on the results of classroom action research, student mastery of the learning material to show improvement. This can be demonstrated by the average daily test results (average daily tests first without STAD cooperative learning) 69 to 72 (daily test II) and 78 (daily test III) after using STAD cooperative learning. Keywords: increased activity, learning outcomes, STAD cooperative